Perubahan Gaya Hidup Terhadap Kesadaran Nasionalisme - Shifa; Setiawati (Universitas Pamulang, 2025)
Lifestyle changes due to technology, urbanization, and globalization have implications for people's nationalist consciousness. This phenomenon is seen in the increased consumption of imported products, the use of social media, and decreased participation in national activities. This study aims to analyze the effect of lifestyle changes on the awareness of nationalism of the people of Kampung Lebong RT/01 RW / 07 Kelurahan Cijoro Pasir. This study involved a population of 141 people with a sample of 105 respondents determined by the Slovin formula. The method used is quantitative with survey approach through Likert scale questionnaire and regression analysis. The results showed a significance value of 0.000 < 0.05, positive regression coefficient 0.265, count 5.085, and R2 of 0.201. This finding proves that lifestyle changes have a positive and significant effect on nationalism awareness with a contribution of 20.1%. In conclusion, modern lifestyles do not necessarily weaken nationalism, but can be an opportunity to strengthen the nation's identity if managed properly. It is suggested that the role of society, government, and education in instilling national values based on local culture and digital technology.